Изменчивость количественных морфологических признаков в популяциях Veronica barrelieri Schott. в условиях антропогенного влияния - Зыбенко, О.В. (Промышленная ботаника, 2004)
Variability of quantitative features of 6 populations of Veronica barrelieri Schott in Donbass under the conditions of anthropogenic press has been studied. It was determined that no distinct differentiation of populations occurs. The complex of anthropogenic factors can make alternations in interpopulational differetiation only by some quantitative features such as the amount of inflorescences. The factor impact on different features is not identical. Variability of the features can be influenced both by habitat conditions and by intrinsic factors – genetic unique character of populations.